2004
DOI: 10.1530/eje.0.1500715
|View full text |Cite
|
Sign up to set email alerts
|

The associations between plasma adiponectin, ghrelin levels and cardiovascular risk factors

et al.

Abstract: Objective: Ghrelin is a recently discovered peptide, which is produced primarily in the stomach. This orexigenic peptide participates not only in the induction of mealtime hunger but also in long-term body weight regulation and energy homeostasis. Adiponectin is a protein secreted by adipocytes, and has been proposed to mediate obesity-related insulin resistance. Moreover, concentrations of adiponectin are reduced in individuals with obesity, insulin resistance and cardiovascular disease. However, human data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
22
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
11
22
2
Order By: Relevance
“…These include serum insulin, total cholesterol, LDL, apoB100, triglycerides, glucose, HbA1c, lower HDL and smaller LDL particle size (27)(28)(29). Our findings are in concordance with the abovementioned results in regard to the negative correlation between adiponectin and WHR, triglyceride concentrations and HbA1c (only in the female subgroup of patients).…”
Section: Discussionsupporting
confidence: 93%
“…These include serum insulin, total cholesterol, LDL, apoB100, triglycerides, glucose, HbA1c, lower HDL and smaller LDL particle size (27)(28)(29). Our findings are in concordance with the abovementioned results in regard to the negative correlation between adiponectin and WHR, triglyceride concentrations and HbA1c (only in the female subgroup of patients).…”
Section: Discussionsupporting
confidence: 93%
“…Moderately negative associations have been reported between adiponectin levels and blood pressure, lipid fractions and triglycerides in women, [35][36][37] and strong associations with the development of insulin resistance and diabetes. [38][39][40] We observed similar associations.…”
Section: Discussionsupporting
confidence: 80%
“…38 Continued study into the possible role of ghrelin in CVD risk is needed. No significant longitudinal associations were identified between resistin levels and cardiovascular risk factor changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cnop et al 5 reported higher adiponectin levels at older ages for 182 healthy men and women, aged 32-75 years, although they did not observe a sex difference. Other investigators have found significant adiponectin increments with age for men, 33,42,43 but four of six reported no age-adiponectin association for women. 7,33,[42][43][44][45] The differences among these studies may relate to the more modest association of age with adiponectin in women, or to the size and ethnic composition of the study populations.…”
Section: Discussionmentioning
confidence: 87%